An update in the therapy of hepatitis C - Díaz Ferrer, Javier (2012)
Hepatitis C is a communicable disease caused by 6 genotypes of the hepatitis C virus, and this condition may have a variable response to therapy. Viral particles are 30-38 nm long, they have an envelope and single-stranded RNA. The virus belongs to the Flaviviridae family. Hepatitis C is a severe public health problem. It has been estimated that the rate of infected persons in most of the countries lies between 1,5 to 3 per cent, and its therapy is quite complex.